Effects of Inoculum Concentrations of Colletotrichum gloeosporioides on Disease Development and Severity on Leaves of Rubber Tree (Hevea brasiliensis) - Sangu, Sangeetha Siva; Muid, Sepiah (Borneo Journal of Resource Science and Technology, 2016)
Colletotrichum gloeosporioides is among the main causal agent of anthracnose of the rubber tree (Hevea brasiliensis). This disease is considered as one of the major foliar diseases that causes declining yields of rubber production in Asia. In order to understand the effect of environmental variables on anthracnose, the effect of inoculum concentrations on the disease development and severity was studied. Spore concentration of 106 spores/ml produced the most prominent disease development. Disease was most severe when the leaves were kept in continuous moisture condition for four weeks. Fungal response study showed that the fungus needed 120 hours after inoculation (hai) to penetrate and colonize leaf cells. Knowledge of this factor on disease development can help improve management tactics based on the control of environmental factors.